2021
DOI: 10.3389/fimmu.2021.793953
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Analysis of Binding and Neutralizing Antibody in COVID-19 Convalescent Patients at 14 Months After SARS-CoV-2 Infection

Abstract: Durability of SARS-CoV-2 Spike antibody responses after infection provides information relevant to understanding protection against COVID-19 in humans. We report the results of a sequential evaluation of anti-SARS-CoV-2 antibodies in convalescent patients with a median follow-up of 14 months (range 12.4-15.4) post first symptom onset. We report persistence of antibodies for all four specificities tested [Spike, Spike Receptor Binding Domain (Spike-RBD), Nucleocapsid, Nucleocapsid RNA Binding Domain (N-RBD)]. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Similar to the findings in ESRD patients with HD after COVID-19 infection, the results in the general population on the dynamics of IgG levels post-COVID-19 infection were inconclusive. Some studies in the general population reported a substantial decline in IgG [54] and neutralizing antibody over 3 months postinfection [55], yet other studies showed a stable antibody level after 6 [56][57][58] to 12 months post-infection [59]. Interestingly, the dynamics of IgG levels following infection in our study were similar to those in ESRD patients with kidney transplantation, who had significant IgG persistence over 3 months after COVID-19 infection [60].…”
Section: Discussionsupporting
confidence: 63%
“…Similar to the findings in ESRD patients with HD after COVID-19 infection, the results in the general population on the dynamics of IgG levels post-COVID-19 infection were inconclusive. Some studies in the general population reported a substantial decline in IgG [54] and neutralizing antibody over 3 months postinfection [55], yet other studies showed a stable antibody level after 6 [56][57][58] to 12 months post-infection [59]. Interestingly, the dynamics of IgG levels following infection in our study were similar to those in ESRD patients with kidney transplantation, who had significant IgG persistence over 3 months after COVID-19 infection [60].…”
Section: Discussionsupporting
confidence: 63%
“…In-house ELISA assays using a panel of purified trimeric complete Wuhan strain (WA1) Spike and Spike-RBD and a panel of VOC Spike-RBD proteins (Beta B.1.351, Delta B.1.617.2, Omicron B.1.1.529) were detailed elsewhere ( 26 28 ). Ab levels were measured using eight 4-fold serial serum dilutions starting at 1:50 and endpoint titers were determined using lastX feature using GraphPad prism area-under-the curve program.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, epidemiological studies indicate that protection against reinfections by natural immunity lasts for over one year with only moderate, if at all, decline over this period. The notion of long-term protection against-reinfections is also underpinned by data on persistance of anti SARS-CoV-2 antibodies and cellular immunity over more than one year in the majority of patients ( Chellamuthu et al, 2021 ; Dehgani-Mobaraki et al, 2021 ; Gussarow et al, 2021 ; Lau et al, 2021 ; Rosati et al, 2021 ).…”
Section: Efficacy and Duration Of Natural Immunity Against Reinfectionsmentioning
confidence: 99%